Investigating the Relationship Between Hotel Employees’ Perception of Organizational Politics (POP) and their Application of Impression Management (IM) Behaviors - Gharib, Rania Hafez (جامعة الإسكندرية - كلية السياحة والفنادق, 2016)
The aim of this study is to examine the relationship between hotel employees’ perception of organizational politics (POP) and their application of impression management (IM) behaviors. Data were collected by developed questionnaire. Originally 300 questionnaires were distributed among employees working in different departments of four and five star hotels in Alexandria. Only 210 questionnaires were returned giving a response rate of 70%. It was found that there was not a significant relationship between employees’ POP and their application of IM behaviors. Also, it was found that there were no significant differences between employees’ gender and age concerning their POP. However, there have been significant differences between employees’ POP in relation to their educational level, hierarchical level and work tenure. Furthermore, there have been significant differences between employees’ application of IM behaviors regarding their age, gender, educational level, hierarchical level and work tenure.
Keywords: الفنادق -- موظفي الفنادق -- السياسة التنظيمية -- إدارة الانطباع -- مدينة الإسكندرية -- مصر